The Janus face of imprisonment: Contrasting judicial conceptions of imprisonment purposes in the European Court of Human Rights and the Supreme Court of the United States. (November 2021) - Dagan, Netanel
This article considers how the Supreme Court of the United States and the European Court of Human Rights apply, interpret and frame abstract imprisonment purposes, and how they view their relevance to prison conditions, while discussing the constitutionality of prison conditions. The article argues that the Supreme Court and the European Court of Human Rights view, conceptualise and interpret the purposes of imprisonment differently. Regarding the purposes of retribution and rehabilitation specifically, the analysis presented in the article exposes a 'Janus face', meaning that each purpose can, and is, interpreted in two different, and almost contrasting ways. The article offers three themes regarding the conceptualisation of imprisonment purposes by the Supreme Court and the European Court of Human Rights: First, the relationship between the purposes of sentencing and imprisonment along the penal continuum, and the role of rehabilitation in a prison regime: should sentencing purposes be relatively static during their implementation in prison, meaning that retributive-oriented sentencing purposes should be pursued (Supreme Court), or should they conversely progress with the passage of time, from retribution to resocialisation as the primary purpose of imprisonment (European Court of Human Rights). Second, the meaning of retributivism in regard to prison conditions: should prisoners pay a debt to society by suffering in restrictive prison conditions (Supreme Court), or is retributivism achieved by atonement and by finding ways to compensate or repair harms caused by crime (European Court of Human Rights). Third, the way in which prison rehabilitation is framed and understood: should prison rehabilitation be seen as a risk management tool aimed purely at lowering recidivism (Supreme Court), or as a moral concept grounded in a prisoner's ability to change his life and belief in personal responsibility for one's actions (European Court of Human Rights). Possible theoretical implications and general policy implications are considered in the article.